2020
DOI: 10.3390/ijms21217955
|View full text |Cite
|
Sign up to set email alerts
|

CCL18 in the Progression of Cancer

Abstract: A neoplastic tumor consists of cancer cells that interact with each other and non-cancerous cells that support the development of the cancer. One such cell are tumor-associated macrophages (TAMs). These cells secrete many chemokines into the tumor microenvironment, including especially a large amount of CCL18. This chemokine is a marker of the M2 macrophage subset; this is the reason why an increase in the production of CCL18 is associated with the immunosuppressive nature of the tumor microenvironment and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 183 publications
2
45
0
Order By: Relevance
“…M2-like macrophages can produce cytokines including TGF-β and IL-10 to promote tumor growth ( 47 , 48 ). In addition, different kind of chemokines from M2-like macrophages including CCL18 and CCL22 mediate immune cells migration to tumor microenvironment ( 49 ). In the present study, we found that PD-1 high ILC2 culture supernatant enhanced the expression of MRC1 (encoding CD206, a typical marker of M2 macrophages) and other M2 macrophage related genes ( TGFB1 , CCL18 , and ARG1 ), and diminished the expression of M1 macrophage related genes ( TNF , IL6 , and CCL5 ).…”
Section: Discussionmentioning
confidence: 99%
“…M2-like macrophages can produce cytokines including TGF-β and IL-10 to promote tumor growth ( 47 , 48 ). In addition, different kind of chemokines from M2-like macrophages including CCL18 and CCL22 mediate immune cells migration to tumor microenvironment ( 49 ). In the present study, we found that PD-1 high ILC2 culture supernatant enhanced the expression of MRC1 (encoding CD206, a typical marker of M2 macrophages) and other M2 macrophage related genes ( TGFB1 , CCL18 , and ARG1 ), and diminished the expression of M1 macrophage related genes ( TNF , IL6 , and CCL5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Amorim et al investigated the role of NLRP3 in human PCM and found that hypoxic cells from patients, which are characterized by the intracellular expression of hypoxia-inducible transcription factor (HIF)-1α, had higher activation of this inflammasome than the control subjects did [ 37 ]. Typically, inflamed tissue has low levels of oxygen, triggering the HIF-1α that up-regulates the IL12B gene to produce more IL-12p40, and inducing Th2 cytokines profile in DCs, which, in turn, favors the secretion of CCL18 [ 58 , 59 ]. Therefore, during active pulmonary chronic PCM, moDCs could have a high expression of HIF-1α and NLRP3, with consequential up-regulation of IL-1β that favors fibrosis and could induce the Th22 response, with IL-21 and IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…This produces another major angiogenic factor called pro-matrix metalloproteinase 9 (proMMP9) ( 125 ). M2 macrophages also facilitate carcinogenesis and metastasis through the production of CCL18 ( 126 ) and the nuclear factor- κB/FAK pathway ( 127 ) leading to induction, migration, invasion, and the EMT. Lastly, TNF is a product of both activated macrophages and the cells of the TME; in addition to being an anti-cancer cytokine, it has been implicated in the inflammatory process necessary for tumor growth ( 128 ).…”
Section: Cells and Components Of The Tme Involved In Suppression Of The Anti-tumor Responsementioning
confidence: 99%